2010
DOI: 10.2478/v10101-010-0002-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two-month walking exercise on bone mass density in young, thin women

Abstract: SummaryStudy aim: To examine the effects of a walking programme on the bone mass density (BMD) in sedentary, thin women aimed at preventing bone losses. Material and methods: Twenty thin (BMI<20) women aged 22.0 ± 1.5 years volunteered to participate in the study. They were randomly assigned into the exercise (n = 10) or control (n = 10) groups, those from the experimental group being submitted to a training programme lasting two months. The programme consisted of 3 walking sessions per week, 30 min each, at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The physical stress stimulates osteoblastic deposition of bone, which causes a negative potential at the compressed site and a positive potential elsewhere in the bone, so BMD increases [16]. The findings of this study come in agreement with the results of a study done by Chow et al [17] who stated an improvement in BMD with treadmill exercise at 80% of HR max . Also, Nelson et al [18] showed useful effects of walking at 75-80% of HR max for 50 minutes, 3-4 times a week on BMD in postmenopausal women.…”
Section: Discussionsupporting
confidence: 91%
“…The physical stress stimulates osteoblastic deposition of bone, which causes a negative potential at the compressed site and a positive potential elsewhere in the bone, so BMD increases [16]. The findings of this study come in agreement with the results of a study done by Chow et al [17] who stated an improvement in BMD with treadmill exercise at 80% of HR max . Also, Nelson et al [18] showed useful effects of walking at 75-80% of HR max for 50 minutes, 3-4 times a week on BMD in postmenopausal women.…”
Section: Discussionsupporting
confidence: 91%
“…Physical effort has a positive effect on the locomotor system: it increases muscle mass and strength, strengthens and stabilizes joints, increases their range of motion, strengthens the muscle attachments, tendons, and ligaments, and prevents joint degeneration [14]. It causes proper bone mineralization [15,16], prevents posture defects, and helps…”
Section: Introductionmentioning
confidence: 99%